PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA OPERASI HITUNG BILANGAN BULAT MELALUI PEMANFAATAN ALAT PERAGA MANIK-MANIK BAGI SISWA KELAS V SD NEGERI 5 GUMELAR - Tugiman (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
Classroom action research that has been done by classroom teacheras the researcher shows that through the use of beads props, motivation andlearning outcomes of Mathematics grade V students of SD Negeri 5 Gumelar inthe first semester of 2012/2013 academic year can be improved. From the initialaverage score of 58.00 with the percentage of students who are able to reach theKKM of 32% can be increased to the average value of 79.10 with the percentageof students who can reach the KKM of 82% in the final conditions. Similarly,student motivation can be improved from the â€œlowâ€ category in the initialcondition to the â€œhighâ€ category in the final condition. Based on the empiricaldata in accordance with the submission of hypotheses based on theoretical studythat is â€œThrough the use of beads props can improve motivation and learningoutcomes Mathematical operations count integers for students of grade V SDNegeri 5 Gumelar in the first semester of 2012/2013â€.